Penerapan Hidden Curriculum PAI dalam Meningkatkan Akhlak Mulia Peserta Tamam English Course (TEC) - Mujahid, Mujahid; Rahmah, Kurniawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2024)
One of the negative impacts of globalization is the erosion of moral values and ethics among students. Globalization is marked by advances in information technology and its various products. The implementation of the Hidden Curriculum (HC) in Islamic Education (PAI) is one of the efforts to preserve moral values and ethics among students. The HC practice at TEC involves instilling discipline and religious awareness. This research employs a qualitative approach with a descriptive method. The informants in this study are teachers and course participants. The researcher plays a key role as the main instrument, engaging directly in data collection at the research site. Data collection techniques include observation, interviews, and document studies. HC PAI practices are carried out in two ways: first, by instilling discipline and second, by promoting religious awareness. This study contributes significantly to improving the ethics of course participants, both in their interactions with peers, teachers, and their parents at home.